Association between Zinc Serum Level And CD4+ Count In Healthy Elderly Women At AISYIAH Elderly Club Kota Gede Yogyakarta - Husni, Niko Adhi; Rochmah, Wasilah; Atmodjo, Suhardi Darmo (Acta Interna The Journal of Internal Medicine, 2012)
ABSTRACTIntroduction. Old ages are associated with physiologic deteriorations of all organs and tissues, such as involution of thymus and decreased function of gastrointestinal tract which lead to malnutrition. Involution of thymus will caused reduction of T cell subset for instance T cell CD4+. Prevalence of nutrient deficiency in old age was high, according to a survey that 35% of subjects with age above 50 years old showed deficiency for one or more vitamins and trace-elements. Zinc as one of trace-elements has vital role for immune system.Aim. Aims of this study are to know the mean of zinc serum level, proportions of zinc deficiency in elderly and correlation between zinc and CD4+ count.Methods and Subjects. Design of this study is cross sectional, with study subjects including healthy elderly women from Aisyiah elderly club at Kota Gede Yogyakarta. Elderly who were eligible with study criteria were measured height, weight, zinc serum level, and CD4+ count. Correlation test was performed to know correlation between ages, weight, body mass index (BMI), and zinc serum level with CD4+ count. Significant variables will be tested with multiple linier regressions. Level of significance is p < 0.05.Results. A total healthy elderly women subjects were 60 persons with median of age 63.5 years old. Median zinc serum level was 5.47 umol/L with range between 3.25- 7.95 umol/L. Zinc deficiency (zinc serum level < 7.65 umol/L) occured in 95% of subjects. Mean of CD4+ count was 767.22±232.95 count/mm3. There were correlations between age, weight, and zinc serum level with CD4+ count (r= -0.296; 0.345; 0.324; 0.792, respectively). Results from linear regression model showed zinc serum level was the only variable that affect to CD4+ count (adjusted R2 = 0.622).Conclusion. Ninety five percent of healthy elderly women at elderly club Aisyiah Kota Gede Yogyakarta suffer from zinc deficiencies, and there is strong correlation between zinc serum level and CD4+ count. Keyword: zinc serum, CD4+ count, elderly